Role of faculty development forums in virtual teaching environment: A case study of marketing research and case group - Sandhu, Rizwan Saleem; Hussain, Sajid (Open praxis, 2016)
The online learning has broadened the teaching spectrum from Face-to-Face to virtual environment, and this move has brought traditional teacher-centered instruction to learner-centered instruction. This paradigm shift appears to place demands on faculty to modify faculty's instruction roles that are different from those encountered in Face-to-Face teaching. This study explores the role of faculty development forum in improving the virtual teaching skills of academic staff members in an online university. The study has used single holistic case study approach, and the data from nine respondents have been collected through an interview schedule divided into four sections of 1) Basic Information, 2) Presentation Skills, 3) Subject Knowledge and 4) Research Orientation as per the objectives of the study. It can be theorized from the findings of the study that in virtual environments where faculty members lack the learning opportunities and exposure available in the conventional environments such forums prove to be very effective in capacity building of the faculty.